(untitled) (Eurasian Scientific Herald, 2023)
The organizational aspects, practical importance and theoretical foundations of the implementation of the pedagogical education cluster are highlighted. The author tried to justify his views with the opinions of Western scientists. The scientific researches of Western scientists regarding the educational cluster are analyzed and the author’s attitude to them is expressed